A proposed music program for the U.P. Elementary School - Teodoro, Concepcion (Pio Roda) 1925- ([Quezon City s.n.], 1966)
This study determined the content of a workable General and Special Music Education program for the UP Elementary School children. The program was developed in terms of the most favorable means of student learning. It consists of graded sequence of experiences from Kindergarten to Grade VI. Suggested materials are chosen to suit the learner's level. The six areas of music learning experiences, namely: singing, listening, rhythm, playing instruments, creative work and music reading were briefly discussed.
Thesis (M.Ed.)--University of the Philippines
Keywords: Music -- Instruction and study